Validation of Lipase and Systemic Inflammatory Response Syndrome as Prognostic Indicators in Pediatric Acute Pancreatitis: A Retrospective Analysis. Issue 3 (March 2019) - Nauka, Peter C.; Weinstein, Toba A.; Dolinger, Michael T.; Miller, Jonathan M.; Kohn, Nina; Bitton, Samuel; Rilo, Horacio L. Rodriguez
ABSTRACT: Introduction: Acute pancreatitis (AP) is understudied in the pediatric population despite increasing incidence. Although many cases are mild and resolve with supportive care, severe acute pancreatitis (SAP) can be associated with significant morbidity and mortality. There is a lack of pediatric-specific predictive tools to help stratify risk of SAP in children. Methods: A retrospective cohort study of patients with AP or recurrent AP at Cohen Children's Medical Center between 2011 and 2016 was performed. Lipase level and the presence of pediatric systemic inflammatory response syndrome (SIRS) on admission were examined as potential predictors of SAP and length of stay (LOS). A multivariate logistic regression or analysis of covariance was used to conduct the multivariate analysis. Results: Seventy-nine pediatric patients met inclusion criteria. Approximately 37% (29/79) had SIRS on admission, 22% (17/79) developed SAP, and there were no mortalities. In both the univariate and multivariate models, SIRS was a predictor of SAP. Mean (SD) LOS for patients with SIRS compared with without SIRS was 9.6 ± 8.3 compared with 6.3 ± 6.9 days ( P  < 0.05). The mean LOS of patients with one or more comorbidity (48%, 38/79) was 10.0 ± 9.5 compared with 5.2 ± 4.0 days ( P  < 0.01) for those patients without any comorbidities. Only the presence of comorbidities predicted length of time spent nil per os (NPO; P  = 0.0022). Patients with comorbidities stayed an average of 5.6 ± 7.6 days NPO, whereas those without comorbidities spent 2.8 ± 2.4 days NPO. Lipase was not predictive of SAP, LOS, or length of time spent NPO. Conclusions: These results support the use of SIRS as a simple screening tool on admission to identify children at risk for the development of SAP. The presence of any comorbidity was predictive of LOS and length of NPO in the multivariate model. This may reflect that comorbidities prolong pancreatitis or influence disposition planning. Abstract : Supplemental Digital Content is available in the text